Isolamento da globulina majoritária, digestibilidade in vivo e in vitro das proteínas do tremoço-doce (Lupinus albus L.), var. Multolupa - Neves, Valdir Augusto [UNESP]; Silva Jr., Sinézio Inácio; Silva, Maraiza Aparecida Da [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2006)
The aim of the present work was to isolate, purify and study some properties of the major globulin fraction from sweet lupin, var. Multolupa; as well as to evaluate the digestibility features of flour and isolated fractions. The protein fractions were separated by differential fractionation with different solvents. The lupin major globulin was isolated, purified by Q-Sepharose chromatography when it showed only one protein peak. The major protein presented a molecular weight of 162.5 ± 10.0 kDa, determined on Sephacryl S-300 chromatography; and subunits between 20 to 70 kDa on SDS-PAGE. The protein solubility in relation to pH and NaCl concentrations showed a typical S-like curve for globulins. The flour and the isolated protein fractions, albumins, globulins and glutelins were evaluated by in vitro and in vivo experiments. The in vitro and in vivo digestibility assays revealed a high digestibility for the globulin, followed by glutelin, albumin and the flour. The globulin in vivo digestibility did not differ significantly from that obtained to casein. Despite the high digestibility encountered for the major protein fraction and protein fractions, the use as the only protein source in the diets revealed low values for RNPR (relative net protein ratio), showing it to be insufficient in terms of sustaining the growth of animals, comparatively to casein.

Os objetivos do trabalho foram isolar, purificar e estudar algumas propriedades da fração globulina majoritária de tremoço-doce, var. Multolupa; assim como avaliar as características de digestibilidade da farinha e frações isoladas. As frações protéicas foram separadas por fracionamento diferencial com uso de diferentes solventes. A globulina majoritária de tremoço-doce foi isolada, purificada por cromatografia em Q-Sepharose, revelando um único pico de proteína. Apresentou um peso molecular de 162,5 ± 10,0 kDa, determinado por cromatografia em Sephacryl S-300, e subunidades entre 20-70 kDa em PAGE-SDS. A solubilidade em função do pH e concentrações de NaCl revelaram curva típica dessa fração. A digestibilidade da proteína da farinha e das frações albumina, globulina e glutelina foi avaliada por experimentos in vitro e in vivo e se revelou alta para a fração globulina, seguida pela glutelina, albumina e farinha. A digestibilidade in vivo da fração globulina, tanto aparente quanto verdadeira, não diferiu significativamente daquela determinada para a caseína. Apesar da alta digestibilidade da fração majoritária e frações protéicas, a utilização como única fonte de proteína nas dietas revelou valores baixos de RPLR (razão protéica líquida relativa), indicando ser insuficiente para sustentar o crescimento dos animais, comparativamente à caseína.
Isolation of major globulin, in vivo and in vitro digestibility of proteins from sweet lupin (Lupinus albus L.) var. Multolupa
Keywords: Lupinus albus; protein fractions; major globulin; in vitro and in vivo digestibility; biological assay; Lupinus albus; frações protéicas; globulina principal; digestibilidade in vitro e in vivo; ensaio biológico